Why does Daphne pseudomezereum drop its leaves in the summer? An adaptive alternative to surviving forest shade. Issue 1 (7th May 2019) - Lei, Thomas; Yamashita, Naoko; Watanabe, Takuya; Kawahara, Takayuki; Miyaura, Tomiyasu
Abstract : Daphne pseudomezereum A. Gray (Dpm) appears to be the only woody species in the north temperate forest that sheds its leaves in the summer while remaining green over winter (i.e. wintergreen leaf habit). Yet, the reason for this odd leaf habit has not been explored. To this end, we examined the microclimatic settings and ecophysiological traits of Dpm and its three native congeners in a field study of eight natural populations. In addition, we conducted a common garden experiment using Dpm plants where potential carbon gain across the seasons was estimated, using actual field microclimate data. Together, these data tested the hypothesis that Dpm retained traits of an open‐grown upland ancestor, unable to adapt to the deep summer shade, it survived by becoming summer dormant and wintergreen. Our hypothesis was supported by patterns of leaf ecophysiological traits and carbon gain simulations in Dpm, consistent with the energetic feasibility of a summer dormancy followed by an autumn leaf sprout. We also conclude that carbon deficit driven by low light and high respiration cost is the trigger for the leaf habit of Dpm and assert that its phenological strategy represents a rare but viable alternative strategy for persistence in the temperate understory.